Towards total protection from impact: a viability study using EPE foam to protect falling eggs. Issue 2 (25th November 2019) - Liu, Gui-Rong; Chen, Guang; Duan, Shu-Yong
Abstract: Total protection of fragile goods and equipment during transport has become critically important as fast delivery systems are growing rapidly due to the rise of mass online commerce worldwide. This paper therefore studies the protection of falling eggs —one of the most fragile goods—through packaging. Intensive experiments are first conducted to obtain the critical stress at which the eggshell is damaged by falling impact. Tests are first conducted of unpackaged eggs dropping onto a granite platform from various heights. Finite element method (FEM) models of unpackaged eggs are then built to simulate the behaviour of eggs and compute their stress levels. The experimental data is compared with the results of FEM simulations to determine the critical stress at which the eggshell is damaged. A series of tests and numerical simulations are then carried out for eggs wrapped in expanded polyethylene (EPE) foam. The stress distribution of both a single egg and multiple eggs in packaging are studied. An empirical formula between the drop speed (or height) and the bottom thickness of the EPE foam packaging is obtained, which can be useful in the design of packaging for the total protection of eggs that may fall during usual transport and delivery operations. The experimental and numerical results from this study show that it is viable to protect fragile goods, as long as the EPE form packaging has sufficient thickness. The proposed study and design procedure are helpful for the selection of key parameters of foam packaging to protect fragile industry products from impact.